2023
DOI: 10.1111/jace.19240
|View full text |Cite
|
Sign up to set email alerts
|

Fast formation of a black inner α‐Al2O3 layer doped with CuO on Al–Cu–Li alloy by soft sparking PEO process

Abstract: Forming high‐temperature α‐Al2O3 phase under soft sparking is an intriguing phenomenon in plasma electrolytic oxidation (PEO) of Al alloys, which contradicts the low energy input of the process. In this study, α‐Al2O3 doped with black CuO is formed beneath an amorphous white outer layer on Al–Cu–Li alloy by PEO in a dilute silicate electrolyte under soft sparking. In comparison, reddish coatings with dominating γ‐Al2O3 are formed under the conventional plasma discharges, although blackish inner layer with α‐Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 104 publications
0
5
0
Order By: Relevance
“…The voltage decreases from 505 V to about 302 V—a voltage drop of 40.19%. He et al [ 22 ] found that the drop increases with increasing current density.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The voltage decreases from 505 V to about 302 V—a voltage drop of 40.19%. He et al [ 22 ] found that the drop increases with increasing current density.…”
Section: Resultsmentioning
confidence: 99%
“…The voltage decreases from 505 V to about 302 V− a voltage drop of 40.19%. He et al [22] found that the drop increases with increasing current density. The fifth stage (Stage E) is the soft spark discharge stage, in which small snow-white sparks are always uniformly distributed on the surface of the sample, and the voltage will again increase with the treatment time.…”
Section: Voltage-versus-time Curves and Spark Morphology Evolution Du...mentioning
confidence: 97%
“…Various surface modification and coating techniques have been applied to suppress the degradation of Mg alloys or even to endow them with improved cytocompatibility [1][2][3][4][5][6][7][8], osteogenesis ability [1][2][3][4][5][6], antibacterial ability [1][2][3][4][5][6], and antitumor ability [7,8]. Among these, micro-arc oxidation (MAO) has received considerable attention, since MAO coatings are generated via in situ oxidation and sintering on magnesium alloys [1,3,4,9], aluminum alloys [10][11][12][13], titanium alloys [14][15][16][17][18], and tantalum alloys [19], and therefore exhibit high hardness, good wear resistance, and corrosion resistance. Most importantly, the composition, structure, papers from 80 to 3000 grits, cleaned with tap and distilled water, and finally dried in an air stream.…”
Section: Introductionmentioning
confidence: 99%
“…Micro-arc oxidation (MAO) is a widely used surface treatment technique to modify magnesium alloys [ 3 , 4 , 5 , 6 ], aluminum alloys [ 7 , 8 , 9 , 10 , 11 , 12 ], titanium alloys [ 13 , 14 , 15 , 16 ], and tantalum alloys [ 17 ] by modulating electrolyte compositions and concentrations [ 18 , 19 , 20 ]. MAO technology can improve the corrosion resistance of magnesium alloys and introduce macro or trace elements such as phosphorus (P) and zinc (Zn) into MAO coating to produce functionalized coating.…”
Section: Introductionmentioning
confidence: 99%